Cross-cultural challenges in international commercial arbitration: Strategies for effective resolution - Tubishat, Bassam Mustafa Abdul-Rahman (Edelweiss Applied Science and Technology, 2024)
The purpose of the article is to determine the most effective strategic guidelines for the implementation of international commercial arbitration. The object of the study is international arbitration. The scientific task is to characterize which strategic guideline is the most optimal today. The research methodology involves the use of the even comparison method. As a result of the study, the most optimal strategic guideline for international commercial arbitration under the pressure of intercultural challenges was determined. In article we prove, that the strategies of Enhanced Cultural Training and Diverse Arbitrator Panels are considered the most effective for addressing cross-cultural challenges in international commercial arbitration for several compelling reasons. The study has a limitation by not taking into account all possible guidelines for development. In further studies, attention should be paid to taking into account the individual needs of specific countries of the world.